Microwave Imaging Using CMOS Integrated Circuits with Rotating 4 × 4 Antenna Array on a Breast Phantom - Hang Song; Afreen Azhari; Xia Xiao; Eiji Suematsu; Hiromasa Watanabe; Takamaro Kikkawa (International Journal of Antennas and Propagation)
A digital breast cancer detection system using 65 nm technology complementary metal oxide semiconductor (CMOS) integrated circuits with rotating 4 × 4 antenna array is presented. Gaussian monocycle pulses are generated by CMOS logic circuits and transmitted by a 4 × 4 matrix antenna array via two CMOS single-pole-eight-throw (SP8T) switching matrices. Radar signals are received and converted to digital signals by CMOS equivalent time sampling circuits. By rotating the 4 × 4 antenna array, the reference signal is obtained by averaging the waveforms from various positions to extract the breast phantom target response. A signal alignment algorithm is proposed to compensate the phase shift of the signals caused by the system jitter. After extracting the scattered signal from the target, a bandpass filter is applied to reduce the noise caused by imperfect subtraction between original and the reference signals. The confocal imaging algorithm for rotating antennas is utilized to reconstruct the breast image. A 1 cm3 bacon block as a cancer phantom target in a rubber substrate as a breast fat phantom can be detected with reduced artifacts.